Halogenated phenolic compounds in wild fish from Canadian Areas of Concern. (4th April 2017) - Gilroy, Ève A.M.; Muir, Derek C.G.; McMaster, Mark E.; Darling, Colin; Campbell, Linda M.; Alaee, Mehran; Brown, Scott B.; Sherry, James P.
Abstract: Concentrations of halogenated phenolic compounds were measured in the plasma of brown bullhead ( Ameiurus nebulosus ) from 4 Canadian Areas of Concern (AOCs), to assess exposure to suspected thyroid‐disrupting chemicals. Hydroxylated polychlorinated biphenyls (OH‐PCBs) were detected in every sample collected in 3 of the AOCs; the detection frequency was lower in samples from the Detroit River AOC. The OH‐PCBs most frequently detected were pentachloro, hexachloro, and heptachloro congeners, which are structurally similar to thyroid hormones. Pentachlorophenol (PCP) was detected at highest concentrations (1.8 ng/g) in fish from Prince Edward Bay, the Bay of Quinte Lake reference site, and Hillman Marsh (the Wheatley Harbour reference site), suggesting local sources of contamination. Elevated PCP concentrations were also detected in the plasma of brown bullhead from exposed sites in the Toronto and Region AOC (0.4–0.6 ng/g). Triclosan was consistently detected in the Toronto and Region AOC (0.05–0.9 ng/g), consistent with wastewater emission. Greater concentrations were occasionally detected in the plasma of brown bullhead from the Bay of Quinte AOC. Concentrations of polybrominated diphenyl ethers were highest in the Toronto and Region AOC, and at 2 of the Bay of Quinte AOC exposed sites near Trenton and Belleville. Distribution patterns reflected the properties and usage of the compounds under investigation and the characteristics of each AOC. Environ Toxicol Chem 2017;36:2266–2273. © 2017 SETAC